СИТУАЦІЙНИЙ ПІДХІД В УПРАВЛІННІ ПЕРСОНАЛОМ СУЧАСНИХ БІЗНЕС-СТРУКТУР - Бойда, Світлана; Запухляк, Володимир (Видавничий дім «Гельветика», 2024)
The article is devoted to the study of the peculiarities of HR management in modern business structures from the point of view of the situational approach. The topic is relevant, as the existing challenges of the macro environment force managers to reconsider traditional approaches to human resources management. Situational management is increasingly being successfully implemented in practice, as exemplified by the cases offered on the official web portal Diia.Business. The purpose of the article is to define the tools of situational personnel management as a factor in the development of business structures in the face of uncertainty in the external environment. To achieve this goal, general scientific and special research methods were used: the method of system analysis - to clarify the essence of the main categories of research; the method of generalization - to identify the main problems of human resources management and situational management tools that can be used to solve them; methods of analysis, synthesis, and classification - to identify specific situational management techniques for certain categories of employees which emerged as a result of military aggression and martial law; empirical method - to identify situational management technologies which have emerged in modern conditions; tabular and graphical methods - to visualize the results of the study. It is determined that the main tools of situational HR management are: HR data analysis; communication tools; online learning platforms; Change Management; health and well-being programs; diversity and inclusion management programs. The authors provide examples of the use of situational personnel management by leading foreign enterprises. The article also draws attention to current domestic trends in personnel management. The article proves the advantages of using situational management for Ukrainian enterprises: this approach will allow preserving human resources in the face of economic shocks. The need for continuous improvement and updating of situational management tools leaves room for further research in this area.
SITUATIONAL APPROACH TO PERSONNEL MANAGEMENT IN MODERN BUSINESS STRUCTURES
Keywords: ситуаційне управління; економічна невизначеність; управління персоналом; бізнес-структура; адаптація